Environmental Requirements for Museums - Ault, Janeen R. (University of Wisconsin-Madison, 2000)
Museums represent a unique class of indoor environments with environmental control requirements that are quite different than traditional occupant-based buildings. As caretakers of cultural and natural artifacts, museums and archives often contain irreplaceable objects. In situations where environments for artifacts are not correctly maintained and controlled, permanent damage can result. A greater understanding of the role that environmental factors play in the preservation of artifacts would help to specify a heating, ventilation and air- conditioning (HVAC) system that meets the special requirements of museums. Five main factors are generally responsible for the deterioration of artifacts: light, temperature, relative humidity, pollution and biological attack. Damage from light can be limited or prevented through the use of UV filters and indirect lighting. Fluctuations in both temperature and relative humidity should be minimized. Although recommended set points for temperature and relative humidity are material dependent, temperature should be maintained in a range between 59-77F with relative humidity between 35-60%. Concentrations of pollutants should be minimized to prevent the formation of harmful acids, which weaken materials. An environmental survey performed at the Field Museum of Natural History in Chicago, IL indicated that the temperature in certain areas often exceeded the recommended upper limit of 77F. Relative humidity was poorly controlled and the central heating caused relative humidities as low as 10% during winter in certain areas of the building. It is very likely that these extremely low relative humidities are a primary cause of damage to the artifacts. Exhibition cases which house artifacts for display provide a layer of protection between the microenvironment within the case and the fluctuations in temperature, relative humidity and pollutant concentration in the Museum macroenvironment. An infiltration model of an exhibition case was developed and validated, in order to calculate the number of air changes a case undergoes in a day. The results indicate that tighter exhibition cases provide greater protection against fluctuations. Cases should therefore be constructed with less than one air change per day. The most obvious solution to the environmental control problems within the Field Museum is a complete retrofit and renovation of the building's HVAC system. To alleviate the severely dry conditions in the Museum during winter until a new HVAC system is installed, any existing humidification equipment must be serviced, cleaned and activated. Obvious leaks in the building perimeter through emergency doors or non-operational windows should be sealed to limit the infiltration of unconditioned outdoor air. The relative humidity of the space can be increased by a few percentage points by reducing the space temperature set point to 68F in the winter.
Under the supervision of Professors Sanford Klein and Douglas Reindl; 173pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 2000.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.